Occupational Health Risks and Hazards Among the Fisherfolk in Kampi Samaki, Lake Baringo, Kenya. (October 2019) - Ngaruiya, Faith Waithera; Ogendi, George Morara; Mokua, Millicent A
Globally, almost 2.78 million deaths that occur annually are attributed to work-related health risks. Worldwide and, especially, in developing countries, about 20% to 50% of the workers are exposed to health risks. Fishing is an ancient occupation, and like many others, it is characterized by numerous health risks and hazards. This study sought to understand the exposure of fisherfolk to human health risks, through fish handling and processing in Lake Baringo, Kenya. The study adopted a cross-sectional social survey design. A systematic random sampling technique was used to select respondents for this study. A semi-structured questionnaire was administered to the respondents to collect data on risks involved during the handling and processing of fish. Key informant interviews and observation checklists were also used to collect more information. Both descriptive and inferential statistics were used to analyze data. Inferential statistics included Pearson χ 2 test, which was used to test the association of various factors on the encounter with occupational health risks. The level of significance was tested at α = 0.05. The study findings reveal the fisherfolk-encountered risks such as cuts, eye irritability, sunburns, skin burn, cold, falls, and musculoskeletal injuries during their work. The results showed that only 12% of the fisherfolk use personal protective equipments (PPEs) at work. Pearson χ 2 test analysis showed there was an association between gender and gender roles (χ 2 = 39.517, P < .05). In addition, an association was revealed between occupational health risks and gender (χ 2 = 16.283, P < .05). There was also an association between occupational hazards and gender (χ 2 = 21.352, P < .05). However, there was no association revealed between occupational health risk and marital status (χ 2 = 1.305, P > .05) and PPEs (χ 2 = 1.089, P > .05). Furthermore, results indicate that 61% of the fisherfolk who suffered from occupational health risks missed work. The study concludes that all the fisherfolk at Kampi Samaki are exposed to various health risks while working, which is thus likely to affect their health. We recommend public health campaigns to sensitize fisherfolk on the associated risks in fish handling and processing. There is also a need for health campaigns for the fisherfolk to appreciate the need for First Aid Kits during the fishing operations.